Plutocracy in the Protocol: A Quantitative Triangulation of Power Concentration in Decentralized Finance Governance - Arya Ganendra; Neva Dian Permana; Muhammad Faiz; Henry Clifford (Enigma in Economics, 2025)
Decentralized Finance (DeFi) proposes a paradigm shift towards a democratized financial ecosystem governed by its users. This vision of decentralization is predicated on the distribution of governance tokens. However, the verity of this claim lacks rigorous empirical validation, raising concerns about a potential "decentralization illusion." This study quantitatively investigates the concentration of governance power within leading DeFi protocols to empirically test this narrative. We employed a multi-faceted quantitative triangulation framework using on-chain data from three archetypal DeFi protocols, selected to represent the core sectors of the ecosystem: a lending market (ProtoLend), a decentralized exchange (ProtoSwap), and a yield aggregator (ProtoYield). Our methodology integrates: (1) Empirical Network Analysis based on on-chain voting power delegation to map the topology of influence; (2) Economic Inequality Metrics, including the Gini Coefficient and Lorenz Curve Analysis, to quantify the distribution of governance tokens; and (3) Systemic Risk Assessment via the Nakamoto Coefficient to determine the minimum number of colluding actors required for a 51% governance attack. The empirical network analysis revealed a distinct core-periphery topology across all protocols, indicative of highly centralized influence structures. This was substantiated by extreme economic inequality, with Gini coefficients of 0.91 for ProtoLend, 0.95 for ProtoSwap, and 0.89 for ProtoYield. Lorenz curves visually confirmed that a minuscule fraction of holders controls the vast majority of voting power. The Nakamoto coefficients were critically low, calculated at 8 for ProtoLend, 5 for ProtoSwap, and 11 for ProtoYield, exposing profound vulnerabilities to collusion and capture. In conclusion, our findings provide robust, triangulated evidence of a pervasive "decentralization illusion" within DeFi. Governance power is not distributed but is instead highly concentrated, replicating the plutocratic power dynamics of traditional finance. This concentration poses significant systemic risks and fundamentally challenges the core value proposition of the DeFi ecosystem.